Social Psychology : A Very Short Introduction - Crisp, Richard J., 1973- (Oxford, New York Oxford University Press, 2015)
Social psychology is the quest to understand how our behaviour is influenced by those around us. Richard Crisp introduces the reader to the history of social psychology, covering the thinkers, discussions and the debates which have shaped its first 120 years, and looks forward to the cutting edge ideas in the discipline.
Include Illustration and Index
Keywords: Social psychology